Traditional Perspective of Mental Disorders Through Kebangru'an Music - Khaerunnisa, Dina (JSSH (Jurnal Sains Sosial dan Humaniora), 2021)
Mental disorders affect a person's ability to think and act. Based on Riskesdas 2018, the number of people with mental disorders in Indonesia reached 9.8%. Indonesian people who still adhere to ancestral culture often use traditional medicine to treat mental disorders. In Benyer Hamlet, Telagawaru Village, East Lombok Regency, mental disorders are treated with traditional medicine, namely through kebangru'an music. Kebangru'an is defined as a spirit that enters the human body, causing behavior that is different from usual. This research uses qualitative research. Data was collected using in-depth interviews, non-participatory observations, and document analysis. The selection of informants was made by purposive sampling. The validity of the data was tested by using the triangulation technique. The research results are the values that the people of Dusun Benyer contain in this kebangru'an music, namely religious values related to dynamism and monotheism beliefs. Moral values are seen as philosophical values in musical instruments and ritual materials. The aesthetic value is seen in the strains of the gending in the kebangru'an music. Further research is needed on the combination of traditional and medical treatment.